2003
DOI: 10.1308/003588403766274962
|View full text |Cite
|
Sign up to set email alerts
|

An audit of post-splenectomy prophylaxis – are we following the guidelines?

Abstract: Conclusions:Results are comparable with other published studies, but are still unsatisfactory for many splenectomy patients. Vaccination rates must be improved and more information given to patients and GPs to allow for appropriate follow-up care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 10 publications
(14 reference statements)
1
22
1
2
Order By: Relevance
“…In 1996, detailed guidelines for prevention and treatment of infection both in asplenic and hyposplenic individuals were published and have been continually updated [7][8][9]. However, accepted best practices have not been implemented in a significant percentage of these patients [7,10,11]. A study published in 2004 of 100 patients between 1990 and 2000 in Beaumont Hospital found that management of the asplenic patient had not followed these guidelines [11].…”
Section: Introductionmentioning
confidence: 99%
“…In 1996, detailed guidelines for prevention and treatment of infection both in asplenic and hyposplenic individuals were published and have been continually updated [7][8][9]. However, accepted best practices have not been implemented in a significant percentage of these patients [7,10,11]. A study published in 2004 of 100 patients between 1990 and 2000 in Beaumont Hospital found that management of the asplenic patient had not followed these guidelines [11].…”
Section: Introductionmentioning
confidence: 99%
“…Compliance with these recommendations is poor worldwide, with recent pneumococcal vaccination rates ranging from 60% to 75%. [1][2][3][4] Therefore, many asplenic patients unnecessarily remain at high risk for OPSI following their splenectomies.…”
mentioning
confidence: 99%
“…Clinical/patient education is one of the measures that can significantly reduce the risk of post-splenectomy sepsis (15). Patients should be aware about post-splenectomy risks and importance of vaccination (11). Higher involvement of all relevant structures dealing with treatment of patients who were subjected to splenectomy (primary health care, public health departments, hospitals) is necessary in order to increase the use of vaccines after splenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The recommendation for patients is to receive a written information about the post-splenectomy risks, medical alert bracelet and up-to-date vaccination card (11,17). In addition, it is necessary to start using splenectomy registers, because then we will be able to follow up all splenectomized patients and increase the adherence to vaccination (18).…”
Section: Discussionmentioning
confidence: 99%